Correlation of tensile strength and corrosion initiation period of reinforced concrete. Issue 1 (1st January 2021) - Mogire, Philip; Mwero, John; Abuodha, Silvester; Mang'uriu, Geoffrey
Abstract: Service life of reinforced concrete constitutes initiation and propagation period. Tensile strength is among the mechanical hardened properties of concrete that influence the corrosion initiation. This research work examines the relationship between split tensile strength and corrosion initiation period of reinforced concrete. The physical and chemical properties of the materials were investigated for compliance for use in reinforced concrete. Concrete of three classes M25, M30 and M35 was cast. For each class, 9 specimens for compression and split tensile strength respectively were prepared and tested at 7, 14 and 28 days. A model for tensile strength was proposed and compared with other models. A parametric study of the critical penetration depth, -a component of the corrosion initiation period, was done using published models. From the results of the study, the proposed and published tensile strength models compare well. It was also noted that the critical penetration depth increases with an increase in tensile strength. The corrosion initiation period linearly increases with the split tensile strength. The tensile strength of concrete can be considered as an input parameter in the initiation period in corrosion service life models.